An Efficient Encoder-Subcarrier Mapping Method Combined With Polar Code for Visible Light Communication - Jing He (IEEE, 2019)
A spectral efficient light emitting diode (LED)-based visible light communication (VLC) system adopting polar-coded 128 quadrature-amplitude modulations (QAM) orthogonal frequency division multiplexing (OFDM) is experimentally demonstrated. To overcome frequency fading in the VLC system, an encoder-subcarrier mapping method is proposed. The experimental results show that, at a sampling rate of AWG with 150 MSa/s, it can realize error-free transmission with high-spectral efficiency (SE) up to 5.77 bit/s/Hz using the proposed method. Its SE is 1.3 times of the un-coded system adopting 16-QAM. At a sampling rate of 175 MSa/s, its measured Q-factor is 9.86 dB, which improves by 5.12 dB compared to the case without coding.